CENTRAL MOTOR CONDUCTION TIME EKSTREMITAS ATAS MENGGUNAKAN TRANSCRANIAL MAGNETIC STIMULATION PADA DEWASA NORMAL - Galuh Absari Utomo,* M. Hasnawi Haddani,* Theodorus* (NEURONA, 2016)
INTRODUCTION TRANSCRANIAL MAGNETIC STIMULATION TMS IS A NONINVASIVE SAFE AND PAINLESS METHOD FOR EVALUATING THE CORTICOSPINAL PATHWAY WHEN TMS IS APPLIED TO THE MOTOR CORTEX AT APPROPRIATE STIMULATION INTENSITY MOTOR EVOKED POTENTIALS MEPS CAN BE RECORDED FROM CONTRALATERAL EXTREMITY MUSCLES